Association study of a brain-derived neurotrophic factor polymorphism and short-term antidepressant response in major depressive disorders - Lung-Cheng Huang; Po See Chen; Eugene Lin; Sen-Yen Hsu (Dove Medical Press, 2008)
Eugene Lin1,7, Po See Chen2,6,7, Lung-Cheng Huang3,4, Sen-Yen Hsu51Vita Genomics, Inc., Wugu Shiang, Taipei, Taiwan; 2Department of Psychiatry, Hospital and College of Medicine, National Cheng Kung University, Tainan, Taiwan; 3Department of Psychiatry, National Taiwan University Hospital Yun-Lin Branch, Taiwan; 4Graduate Institute of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 5Department of Psychiatry, Chi Mei Medical Center, Liouying, Tainan, Taiwan; 6Department of Psychiatry, National Cheng Kung University Hospital, Dou-liou Branch, Yunlin, Taiwan; 7These authors contributed equally to this workAbstract: Major depressive disorder (MDD) is one of the most common mental disorders worldwide. Single nucleotide polymorphisms (SNPs) can be used in clinical association studies to determine the contribution of genes to drug efficacy. A common SNP in the brain-derived neurotrophic factor (BDNF) gene, a methionine (Met) substitution for valine (Val) at codon 66 (Val66Met), is a candidate SNP for influencing antidepressant treatment outcome. In this study, our goal was to determine the relationship between the Val66Met polymorphism in the BDNF gene and the rapid antidepressant response to venlafaxine in a Taiwanese population with MDD. Overall, the BDNF Val66Met polymorphism was found not to be associated with short-term venlafaxine treatment outcome. However, the BDNF Val66Met polymorphism showed a trend to be associated with rapid venlafaxine treatment response in female patients. Future research with independent replication in large sample sizes is needed to confirm the role of the BDNF Val66Met polymorphism identified in this study.Keywords: antidepressant response, brain-derived neurotrophic factor, major depressive disorder, serotonin and norepinephrine reuptake inhibitor, single nucleotide polymorphisms